Akibat Hukum Atas Kelalaian Tenaga Kesehatan Dalam Memberikan Obat Kadaluarwarsa Di Kota Kupang - Inggrid Modok; Yossie M Y Jacob; Helsina F Pello (Law Faculty, Nusa Cendana University, 2026)
Health law is needed to regulate health problems in order to create order in life, health law is all legal rules directly related to health maintenance and the application of rules and regulations in civil law instruments, criminal law, as long as these rules regulate legal relations in health care. There are still many problems related to health in Indonesia, one of which is health workers who give the wrong medicine to patients. Based on the above explanation, the author researched with the aim of (a) To find out the legal consequences of negligence of health workers in administering expired drugs b) To find out the imposition of legal sanctions from the Health Service to health workers who provide expired drugs in Kupang City.The research method used in this study is empirical juridical. In terms of this research, it is carried. The imposition of sanctions from the Health Office on health workers who provide expired drugs, sanctions applied to health workers or pharmacists who make mistakes or negligence in administering drugs so that patients or in this case consumers suffer material, physical losses and even death, then the sanctions that can be given are administrative sanctions in the form of reprimands until the freezing of health workers' permits then civil sanctions in the form of replacements losses in terms of unlawful acts and defaults, even criminal sanctions in the form of physical punishment, namely imprisonment for a certain period of time.